MAD1: Kinetochore Receptors and Catalytic Mechanisms - Luo, Yibo; Ahmad, Ejaz; Liu, Song-Tao (Frontiers in Cell and Developmental Biology, 2018)
The mitotic checkpoint monitors kinetochore-microtubule attachment, delays anaphase onset and prevents aneuploidy when unattached or tensionless kinetochores are present in cells. Mitotic arrest deficiency 1 (MAD1) is one of the evolutionarily conserved core mitotic checkpoint proteins. MAD1 forms a cell cycle independent complex with MAD2 through its MAD2 interaction motif (MIM) in the middle region. Such a complex is enriched at unattached kinetochores and functions as an unusual catalyst to promote conformational change of additional MAD2 molecules, constituting a crucial signal amplifying mechanism for the mitotic checkpoint. Only MAD2 in its active conformation can be assembled with BUBR1 and CDC20 to form the Mitotic Checkpoint Complex (MCC), which is a potent inhibitor of anaphase onset. Recent research has shed light on how MAD1 is recruited to unattached kinetochores, and how it carries out its catalytic activity. Here we review these advances and discuss their implications for future research.